Comparative phytotoxicity of Azolla pinnata and Lemna minor in Treated Palm Oil Mill Effluent - Binti Abd Kadir, Azlin; Rozaimah Sheikh Abdullah, Siti; Abu Hasan, Hassimi (International Journal of Engineering and Technology, 2018)
The phytotoxicity of Azolla pinnata and Lemna minor was assessed when exposed To Treated Palm Oil Mill Effluent (POME) for their survival and growth tolerance in a 5-day exposure conducted in an open laboratory at Universiti Kebangsaan Malaysia. A total of 34 100 mL-containers were used, with three replicates for each concentration, including plant less control and plant control. 50 mL of treated POME in different concentrations (100%, 75%, 50% and 25%) was filled in each container and exposed to 3 g Azolla pinnata or Lemna minor with observation conducted daily. After two days of exposure, 40% of A. pinnata died in 100% concentration and almost 100% died after 5 days of exposure for all concentrations. On L. minor, only 5% mortality was observed for 100% concentration on the fourth day and remained healthy until the end of five days. At the end of 5-day phytotoxicity exposure, the highest removals were 63.0%, 70.5%, 51.0%, 65.4% and 53.8% respectively for COD, BOD, Ammonia, Phosphate And Nitrates by A. pinnata, while the maximum removals recorded by L. minor were 61.0%, 54.0%, 9.8%, 61.4% and 31.6% respectively, giving evidence that A. pinnata is more effective in removing pollutants than L. minor although its survival in the treated POME is lesser than L. minor.Â Â
Keywords: Azolla Pinnata; Lemna Minor; Phytotoxicity; Palm Oil Mill Effluent (POME